Bilateral Tuba Ovarian Tuberculosis Mimicking Ovarian Carcinoma in an 18 Year Old Woman - Iskandar, Harun; Setiawati, Dewi; Handayani Idrus, Hasta (Journal of Neonatal Surgery, 2025)
Background: Tuba-ovarian tuberculosis (TB) is a rare extrapulmonary form of tuberculosis that can closely mimic ovarian carcinoma, posing a diagnostic challenge due to similar clinical and imaging presentations. This case highlights the importance of considering TB in the differential diagnosis of adnexal masses, particularly in young women from TB-endemic areas. Case Presentation: An 18-year-old woman presented with chronic pelvic pain, abdominal distension, low-grade fever, and significant weight loss over three months. Clinical examination revealed a palpable pelvic mass. Laboratory findings showed elevated CA-125 levels (420 U/mL), raising suspicion of ovarian carcinoma. Imaging studies, including pelvic MRI, demonstrated bilateral adnexal masses with ascites and omental thickening, findings suggestive of advanced ovarian malignancy. Exploratory laparotomy revealed bilateral tubo-ovarian masses, dense adhesions, and caseous material. Histopathological examination confirmed granulomatous inflammation, and Ziehl-Neelsen staining identified acid-fast bacilli. Molecular testing (GeneXpert) confirmed the presence of Mycobacterium tuberculosis. The patient was diagnosed with bilateral tuba-ovarian tuberculosis and initiated on anti-tubercular therapy (ATT). Follow-up after six months showed significant clinical improvement, resolution of masses, and normalization of CA-125 levels. Discussion: This case underscores the difficulty in differentiating tuba-ovarian tuberculosis from ovarian carcinoma based solely on clinical, serological, and imaging findings. Early histopathological and microbiological evaluation is critical to avoid misdiagnosis and unnecessary extensive surgical interventions. Conclusion: Tuba-ovarian tuberculosis, although rare, should be included in the differential diagnosis of adnexal masses in young women, particularly in TB-endemic regions. Timely recognition and treatment can lead to favorable outcomes, preventing undue morbidity.